Nature of disorderliness in Child Custody - A. Aliabadi; A. Aliabadi (مطالعات فقه و حقوق اسلامی, 2012)
In spite of all hardships and difficulties, child custody is really enjoyable. Therefore, parents will have custody of the children. It is their Legal right and duty. Parents undertake this responsibility together as long as their joint life will continue regardless of priorities. If their Joint life doesn't continue, child custody is necessarily left to one of them. In order to provide the spiritual and mental needs of children as well as father or mother deprived of child custody an appointment will be made. Sometimes father or mother who has authority over child prevents meeting and sometimes he or she is not ready to separate from child under no circumstance and insists on staying with child. Due to apparent conclusion of regulations of three articles of three different Acts, nature of mentioned refusal has rotated between penal and civil attributes and competent courts have also fallen into suspicion. I, the writer of this article, looking attentively at laws and essentials have come to this conclusion that the nature of act is civil and competent court is family court.